PENGARUH KOMPETENSI APARATUR PENATA LAPORAN KEUANGAN DAN PERAN APARAT PENGAWAS INTERN PEMERINTAH (APIP) TERHADAP KUALITAS LAPORANKEUANGAN PEMERINTAH DAERAH DI PROVINSI BENGKULU - Irwansyah Irwansyah; Tantri Wulandari (UNIB Press, 2018)
apparatus internal government (apip) on quality of local government financial report in bengkulu province. This research uses quantitative approach, using primary data through questionnaire. Respondents in this study are the Financial Administration Official (PPK), the Technical Activity Executing Officials (PPTK), and the Spending Treasurer. Technical analysis of data using multiple linear regression analysis of SPSS program assistance. The results of this study indicate that the competence of the apparatus of financial statements do not positively affect the quality of local government financial and the role of apparatus internal government (APIP) has a positive effect on the quality of local government financial statements in Bengkulu Province.Key Words: Government, Competency, APIP